The Influence of Thermomagnetometric Measurement Conditions on the Recorded Curie Temperature of Cobalt-Zinc Ferrite; Emerging Trends in Materials Research and Manufacturing Processes - Nikolaev E. V. Evgeny Vladimirovich; Lysenko E. N. Elena Nikolaevna; Surzhikov A. P. Anatoly Petrovich; Bobuyok S. A. Sergey Andreevich (2023, 2023)
The influence of the measurement atmosphere, heating and cooling rate on the Curie temperature of Co0.5Zn0.5Fe2O4 cobalt-zinc ferrite was studied by thermogravimetric analysis in a magnetic field. This technique allowed determining the temperature of ferrimagnet-paramagnet transition at Curie point of magnetic materials. The method of solid-phase synthesis was used to produce the Co–Zn ferrite. Curie temperature control of the ferrite was carried out by using a Netzsch STA 449C Jupiter thermal analyzer. Measurements were performed in the temperature range of 45–400 °C with heating (cooling) rates of 10, 20, and 50 K/min. The cell of analyzer was purged with air or nitrogen. According to thermomagnetometric analysis, the Curie temperature of Co–Zn ferrite are in the range of 171–188 °C, depending on the experimental conditions. It was shown, that the Curie temperature weakly depends on both the heating and cooling rate during thermogravimetric analysis in a magnetic field. However, this parameter depends on the measurement mode